Science Opportunities for IMAP-Lo Observations of Interstellar Neutral Hydrogen and Deuterium during a Maximum of Solar Activity - M. A. Kubiak; M. Bzowski; E. Möbius; N. A. Schwadron (The Astrophysical Journal Supplement Series, 2024)
Direct-sampling observations of interstellar neutral gas, including hydrogen and deuterium, have been performed for more than one cycle of solar activity by IBEX. The IBEX viewing is restricted to directions perpendicular to the spacecraft–Sun line, which limits the observations to several months each year. This restriction is removed in the forthcoming mission called Interstellar Mapping and Acceleration Probe. The IMAP-Lo instrument will have the capability of adjusting the angle of its boresight with the spacecraft rotation axis. We continue a series of studies of the resulting science opportunities. We adopt the schedule of adjusting the boresight angle suggested by Kubiak et al. and focus on interstellar hydrogen and deuterium during solar maximum. Based on an extensive set of simulations, we identify the times during the calendar year and the elongation angles of the boresight needed to measure the abundance of D/H at the termination shock and to unambiguously observe interstellar H without a contribution from interstellar He. Furthermore, IMAP-Lo will be able to resolve the primary and secondary populations, in particular, to view the secondary population with little contribution from the primary. We show that the expected signal is sensitive to details of radiation pressure, particularly its dependence on the radial speed of the atoms, and to details of the behavior of the distribution function of the primary and secondary populations at the heliopause. Therefore, IMAP-Lo will be able to provide the observations needed to address compelling questions in heliospheric physics and even in general astrophysics.